The Impact of Implementing the Contextual Learning Model on Students' Interest in Learning Islamic Religious Education at Ibnu Abbas As-Salafy Islamic Boarding School - Andrey Fajar Albineri; Sukari Sukari (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to determine the effect of applying the Contextual Teaching and Learning (CTL) model on students' learning interest in Islamic Religious Education (PAI) subjects at Pondok Pesantren Ibnu Abbas As Salafy Sragen. The background of this research stems from the low learning interest of students in PAI, as indicated by the lack of active participation and limited connection between learning materials and real-life experiences. This study employed a quantitative approach with an associative research design. Data were collected through questionnaires distributed to 137 students at the Wustha and Madrasah Aliyah levels using purposive sampling. The data were analyzed using correlation tests, simple linear regression, and the coefficient of determination. The results show that the implementation of the CTL model has a significant effect on students' learning interest, with a correlation coefficient of 0.575 and a determination coefficient of 57.5%, indicating a moderately strong positive relationship. It can be concluded that the CTL model effectively enhances students' interest in learning PAI through active, relevant, and meaningful learning experiences. This finding is expected to serve as a reference for PAI teachers in applying innovative learning strategies in Islamic boarding schools.